ANALISIS POTENSI JEJAK KARBON LIMBAH CAIR DAN LISTRIK PADA PROSES PENYAMAKAN KULIT - Aditya Wahyu Nugraha; Ono Suparno; Nastiti Siswi Indrasti (Department of Agroindustrial Technology, Bogor Agricultural University, 2020)
Leather is a product obtained from the conversion process of raw skin/hide into leather. The process generate a number of wastes with a high pollutant content, especially waste water. The waste contributes to the formation of carbon emission. Awareness on environmental sustainability also requires the industry to improve its production system to make it more eco-friendly. Improvements will increase production and the industry reputation. Before making improvements to the production system, it is necessary to carry out an analysis related to the carbon emissions produced in producing a product. The objectives of this study were to calculate carbon emission (carbon footprint) that generates in the leather tannery process and to give alternative strategy for the environmental improvement. The research used primary data and secondary data. This research was carried out with the processes identification, carbon emission sources identification, an analysis of the carbon emission potential amount, and a study of strategies to minimize carbon formation in the tannery. The results of the analysis showed that electricity and wastewater were sources of carbon in the production process of leather. The total of carbon emission formed in the leather tanning process was 1,692.17 kg CO2 eq per batch, where wastewater contributed more than electricity. Further analysis showed that 1 m2 of leather produced 8.08 kg CO2 eq of carbon. The strategies that can be taken to reduce carbon emissions are engineering processes, material substitution, and using eco-friendly materials. Keywords: carbon footprint, leather, tannery